Sliding Wear Properties of a Composite of Aluminum 2024 Powder Reinforced with Heat Treatment and Silicon Carbide - Mahdi, Ahmed Sahib (Journal of Engineering and Technological Sciences, 2018)
Wear behavior of aluminum alloy 2024 was investigated. Three patterns of specimens, namely, fabricated (compacted), reinforced with silicon carbide only and reinforced with silicon carbide followed by heat-treatment (quenching and aging processes) were selected. The effect of load on the specimen was studied for each type of pattern. Three values of load (10, 12.5 and 15N) were tested to investigate the wear behavior. The experimental results showed that the weight loss was 0.056 g for the specimen reinforced with silicon carbide and heat treatment, while it was 0.069 and 0.067 g for the as-fabricated specimen and the specimen reinforced with silicon carbide only, respectively. The increase of microhardness caused increased wear resistance and thus the weight loss was reduced. The microhardness increased with the increase of the ratio of silicon carbide, while, conversely, the density decreased with the increase of the ratio of silicon carbide. The maximum value of hardness was observed for the specimen reinforced with 5% of Sic followed with heat treatment at 284 Hv, while for the specimens reinforced with 4% and 3% Sic it was 255 and 227 Hv, respectively. It can be concluded that when heat treatment and reinforcement by Sic particles are performed, the microhardness value of aluminum 2024 will increase.